Tennis without lessons - Brown, Jim, 1940-. (Englewood Cliffs, N. J. : Prentice-Hall, 1977)
A guide for beginning and intermediate tennis players using a teach-yourself approach. Discusses rules, strokes, strategy, improving without playing, recognizing and correcting problems, and playing intelligently.
Includes index.
Bibliography: p. 153-154.
Keywords: Tennis